Airway opening pressure maneuver to detect airway closure in mechanically ventilated pediatric patients - Rodriguez Guerineau, Luciana; Vieira, Fernando; Rodrigues, Antenor; Reise, Katherine; Todd, Mark; Guerguerian, Anne-Marie; Brochard, Laurent (Frontiers in Pediatrics, 2024)
Background: The complete collapse of the airway known as airway closure has been described under mechanical ventilation during anesthesia and recently in adult patients with acute respiratory distress syndrome (ARDS). A ventilator maneuver can identify airway closure and measure the pressure at which the airway re-opens (Airway Opening Pressure, AOP). Without that maneuver, AOP is unknown to clinicians. Objective: To demonstrate the technical adaptation of the adult maneuver for children and illustrate its application in two cases of pediatric-ARDS. Methods: A bench study was performed to adapt the maneuver for 3-50 kg patients. Four maneuvers were performed for each simulated patient, with 1, 2, 3, and 4 seconds of insufflation time to deliver a tidal volume (Vt) of 6 mL/kg by a continuous flow. Results: Airway closure was simulated and AOP was visible at 15 cmH2O with a clear inflection point, except for the 3 kg simulated patient. Regarding insufflation time, a 4 sec maneuver exhibited a better performance in 30 and 50 kg simulated patients since shorter insufflation times had excessive flowrates (>10 L/min). Below 20 kg, the difference in resistive pressure between a 3-sec and a 4-sec maneuver was negligible, therefore prolonging the maneuver beyond 3 sec was not useful. Airway closure was identified in two p-ARDS patients, in the 28 kg-patient using the pediatric maneuver. Conclusions: We propose a pediatric AOP maneuver delivering 6mL/kg of Vt at a continuous low flow inflation for 3 sec for patients up to 20 kg and for 4 sec above 20kg.